A Domain-Analytic Perspective on Sexual Health in LCSH and RVM - Fortier, Alexandre; McTavish, Jill (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper analyses and compares the treatment of sexual health in Library of Congress Subject Headings and Répertoire de vedettes-matière de l’Université Laval using three of Bowker and Star’s (1999) infrastructural inversion techniques: practical politics, convergence, and resistance. Cette communication propose une analyse comparative du traitement de la santé sexuelle dans les Library of Congress Subject Headings et le Répertoire de vedettes-matière de l’Université Laval à l’aide de trois des techniques d’inversion structurelle de Bowker et Star (1999) : les politiques concrètes, la convergence et la résistance.